Tajik Language and its Influence on Western Europeаn Languages - Zheng, ZHONGYI; BIKTAGIROVA, Zubayda Albertovna; HABIBOVICH, Kasimov Olimjon (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Based on reliable linguistic sources, this article studies lexical units of the Tajik language borrowed by Western European languages at different periods of development. Lexemes indicate that the Tajik language had close contacts with Western European languages at different stages of its development. One of the important sources of influence of the Tajik language should be considered the outstanding monument of world literature “Shahnameh” by Abulkasim Firdousi (Xth century). On this basis, the study of vocabulary and terminology of “Shahnameh” is relevant not only for Tajik linguistics but also for Indo-European ones, including Western European languages. RESUMEN Basado en fuentes lingüísticas confiables, este artículo estudia unidades léxicas del idioma tayiko prestadas por las lenguas de Europa occidental en diferentes períodos de desarrollo. Los lexemas indican que el idioma tayiko tuvo contactos cercanos con las lenguas de Europa occidental en diferentes etapas de su desarrollo. Una de las fuentes importantes de influencia del tayiko debe considerarse el monumento sobresaliente de la literatura mundial "Shahnameh" por Abulkasim Firdousi (siglo X). Sobre esta base, el estudio del vocabulario y la terminología de "Shahnameh" es relevante no solo para la lingüística tayiko sino también para la indoeuropea, incluidas las lenguas de Europa occidental.